2005
DOI: 10.1016/j.atmosenv.2005.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Microbial population in cloud water at the Puy de Dôme: Implications for the chemistry of clouds

Abstract: et al.. Microbial population in cloud water at the Puy de Dôme: implications for the chemistry of clouds. Atmospheric Environment, Elsevier, 2005, pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
156
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(168 citation statements)
references
References 29 publications
7
156
0
5
Order By: Relevance
“…In addition, bacterial and fungal OTUs characterizing atmospheric deposition (rain and aeolian dust) consisted of either pathogenic epiphytic (Aureobasidium) or highly versatile microorganisms (Methylobacterium, Pseudomonas and Sphingomonas) predominantly associated with plants (Vorholt, 2012). Representatives of these bacterial genera have also been found in cloud droplets (Amato et al, 2005), in hailstones (Šantl-Temkiv et al, 2012) and in aerosols collected at high altitude (Bowers et al, 2012). Similarly, OTUs present in snow, such as representatives of the Chlamydomonadaceae and Acetobacteraceae families, were mostly absent from other endogenous glacial habitats or barren soils.…”
Section: Origin Of Microbial Pioneers In Deglaciated Soilsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, bacterial and fungal OTUs characterizing atmospheric deposition (rain and aeolian dust) consisted of either pathogenic epiphytic (Aureobasidium) or highly versatile microorganisms (Methylobacterium, Pseudomonas and Sphingomonas) predominantly associated with plants (Vorholt, 2012). Representatives of these bacterial genera have also been found in cloud droplets (Amato et al, 2005), in hailstones (Šantl-Temkiv et al, 2012) and in aerosols collected at high altitude (Bowers et al, 2012). Similarly, OTUs present in snow, such as representatives of the Chlamydomonadaceae and Acetobacteraceae families, were mostly absent from other endogenous glacial habitats or barren soils.…”
Section: Origin Of Microbial Pioneers In Deglaciated Soilsmentioning
confidence: 96%
“…However, recent studies have reported that the atmosphere harbours complex and viable microbial communities (Vaïtilingom et al, 2010;Šantl-Temkiv et al, 2012;Stres et al, 2013). For example, Amato et al (2005) isolated active bacteria and fungi from cloud droplets. Similarly, Šantl-Temkiv et al (2013) reported that viable methane-oxidizing bacteria were found in rain and Favet et al (2013) retrieved living algae (for example, Chlorella) and fungi (for example, Aspergillus) in wind-blown desert dust.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a history of research examining bacterial distributions in the near-surface atmosphere (Lighthart and Shaffer, 1995a, b;Lighthart, 1997;Tong and Lighthart, 1998), the majority of this work has largely been restricted to surveys of culturable bacteria (those bacteria which can readily be grown and isolated under laboratory conditions). As most bacteria cannot be readily cultured (Pace, 1997), the vast majority of airborne bacteria have effectively been excluded from these culture-based studies (Amato et al, 2005) and comprehensive surveys of airborne bacterial diversity are uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…In the second numerical experiment (S2 scenario), homogeneous nucleation occurred and IN concentration was assumed to be 100 000 times less than the total population of bacteria observed by Amato et al (2005) at a temperature range of −12 to −2 • C, where we adjust a polynomial equation between these two extremes. Only a fraction of total bacteria can act as IN , therefore it was set at 1 INA per m 3 of cloud volume (see Fig.…”
Section: Ice Nucleation Modelingmentioning
confidence: 99%
“…According to Amato et al (2005), the total bacterial density in clouds is about 3×10 4 cells m −3 of cloud volume (1× 10 5 cells ml −1 of cloud water) based on direct visual counts of total cells. Most of the isolated micro-organisms, including 12 fungal and 17 bacterial strains, were described for the first time in atmospheric water by Amato and colleagues.…”
Section: Introductionmentioning
confidence: 99%